Peran Sikap Dalam Memediasi Pengaruh Online Review dan Live Steraming Terhadap Niat Beli Ulang Produk Fashion Pada E-Commerce - Luh Riska Febrianti, Ni; Adi Permadi, Lalu; Rispawati, Dewi (Postgraduate, University of Mataram, 2025)
This study aims to analyze the role of attitude in mediating the influence of online reviews and live streaming on repurchase intentions for fashion products in e-commerce. The data were collected using a questionnaire with a sample of 120 respondents. The analysis was conducted using Structural Equation Modeling (SEM) with the SmartPLS v.4.0 tool. The results of this study indicate that, first, attitude has a positive and significant effect on repurchase intentions. Second, online reviews have a negative and insignificant effect on repurchase intentions. Third, live streaming has a positive but insignificant effect on repurchase intentions. Fourth, online reviews have a positive and significant effect on repurchase intentions. Fifth, online reviews positively and significantly affect repurchase intentions through attitude. Sixth, live streaming positively and significantly affects repurchase intentions through attitude. The findings can be used as a basis for increasing repeat purchases by improving the quality of online reviews, live streaming, and fostering positive consumer attitudes.